Antibody–drug conjugates harboring a kinesin spindle protein inhibitor with immunostimulatory properties. (31st December 2022) - Sommer, Anette; Berndt, Sandra; Lerchen, Hans-Georg; Forveille, Sabrina; Sauvat, Allan; Mumberg, Dominik; Kroemer, Guido; Kepp, Oliver
ABSTRACT: Antibody–drug conjugates (ADCs) are used to target cancer cells by means of antibodies directed to tumor-associated antigens, causing the incorporation of a cytotoxic payload into target cells. Here, we characterized the mode of action of ADC costing of a TWEAKR-specific monoclonal antibody conjugated to a small molecule kinesin spindle protein (KSP) inhibitor (KSPi). These TWEAKR-KSPi-ADCs showed strong efficacy in a TWEAKR expressing CT26 colon cancer model in mice. TWEAKR-KSPi-ADCs controlled the growth of CT26 colon cancers in immunodeficient as well as in immunocompetent mice. However, when treated with suboptimal doses, TWEAKR-KSPi-ADCs were still active in immunocompetent but not in immunodeficient mice, indicating that TWEAKR-KSPi-ADCs act – in addition to the cytotoxic mode of action – through an immunological mechanism. Indeed, in vitro experiments performed with a cell-permeable small molecule KSPi closely related to the active payload released from the TWEAKR-KSPi-ADCs revealed that KSPi was capable of stimulating several hallmarks of immunogenic cell death (ICD) on three different human cancer cell lines: cellular release of adenosine triphosphate (ATP) and high mobility group B1 protein (HMGB1), exposure of calreticulin on the cell surface as well as a transcriptional type-I interferon response. Further, in vivo experiments confirmed that treatment with TWEAKR-KSPi-ADCs activated immune responses via enhancing the infiltration of CD4 + and CD8 + T lymphocytes in tumors and the local production of interferon-γ, interleukin-2, and tumor necrosis factor-α. In conclusion, the antineoplastic effects of TWEAKR-KSPi-ADCs can partly be attributed to its ICD-stimulatory properties.